INDUSTRI RUMAHAN BANK SAMPAH PENGARUHNYA TERHADAP PERUBAHAN SOSIAL (STUDI PADA BANK SAMPAH DI KELURAHAN REJOSARI KECAMATAN BUKIT RAYA KOTA PEKANBARU) - Hanifa Rahmadani; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out In the village of Bukit Raya subdistrict of Rejosari Pekanbaru. The purpose of this research is to know the working system in Bank cottage industry of garbage in the village of Bukit Raya subdistrict of Rejosari Pekanbaru. The topic of this research focus is the social changes that occurred in the Bank industry workforce of garbage in the village of Bukit Raya subdistrict of Rejosari Pekanbaru. This research uses the theory of social change. The sample in this study amounted to 6 people. The author uses qualitative methods and use techniques the taking of purposive Sampling. Data instruments are observation, interview and documentation. From the research that is done, the authors find that the Bank's Trash Industry Mastermind Collection was established in 2007. Since its establishment, the Bank Trash Mastermind Collection is already moving and empowering the community in social and economic fields. Work system applied by the mastermind Collection: collecting second-hand, thrift, cleaners and tailors the pattern of recycled products. Workers who collect used goods are generally used to work as a scavenger. Every day they collect used goods in the form of used plastic bottles and wrap food to be recycled by the mastermind Collection. Stages of rubbish piled the stuff done with the wash of disused plastic bottles with water and SOAP and then in dry. After dried litter the former in form and made patterns for sewn and produced. Of the research also found that there were some changes that happened to the workforce in the mastermind Collection, namely: social change, economic change and cultural change.  Keywords: Bank Trash, Social Change